Expert Consensus on Clinical Application of Lower Limb Rehabilitation Robots - ZHANG Lixin; BAI Dingqun; BAI Yulong; CHEN Wenhua; CHEN Yan; DU Qing; FAN Maohua; HE Hongchen; HUANG Liping; JIA Jie; LI Jianhua; LI Lei; et al. (康复学报)
With the gradual increase in the application of lower limb robots in motor function rehabilitation, there is a need to standardize the clinical application of lower limb rehabilitation robots in China. This consensus integrates the characteristics of lower limb rehabilitation robots applications in the treatment for patients with hemiplegia, paraplegia, cerebral palsy, and other common lower limb dysfunctions in China. In addition, referencing the latest research, this consensus elaborates on the working principles, classification, clinical application (indications and contraindications, working parameters and operating procedures, safety), and recommendations on clinical application (hemiplegia, paraplegia, musculoskeletal diseases, childhood diseases and other systemic diseases) when using lower limb rehabilitation robots in the current context. Lower limb rehabilitation robots are well-suitable for patients with walking difficulties and long-term bedridden condition. According to the patient's posture during rehabilitation training, they can be classified into sitting or supine robots, upright robots, and assisted upright robots. The treatment parameters of lower limb robots are determined by the patient's weight and lower limb's length, range of motion, and muscle strength, among which guiding force, walking speed, and anti-gravity are important parameters that need to be adjusted. There are many factors that affect the safety using of lower limb rehabilitation robots, and it is usually necessary to evaluate the safety by monitoring the occurrence of adverse events during robot training. Studies have shown that combining lower limb rehabilitation robot training with conventional rehabilitation therapy or emerging rehabilitation technologies such as virtual reality and transcranial direct current stimulation improves motor function in stroke patients with hemiplegia. However, determining whether its training effect is superior to conventional rehabilitation therapy requires further clinical study (high-level evidence). Studies have also shown that lower limb rehabilitation robot training can improve walking function (medium to high-level evidence), cardiopulmonary function (low to medium-level evidence), lower urinary tract function (low-level evidence), and balance function (low to medium-level evidence) in paraplegic patients. Medium-level evidence suggests that paraplegic patients with lower limb spasms can undergo lower limb rehabilitation robot training. Studies have shown that lower limb robot training can improve the pain, range of motion, muscle strength of lower limb, and walking ability of patients with musculoskeletal diseases. It is mainly used in post-total knee arthroplasty (medium-level evidence), post-total hip arthroplasty (medium to low-level evidence), and osteoarthritis (medium to low-level evidence). Studies have shown that lower limb rehabilitation robot assisted gait training (medium-level evidence) and joint activity training (low-level evidence) are beneficial for improving lower limb function, gross movement, and gait in children. Lower limb robot assisted gait training combined with exercise therapy (medium-level evidence) can help improve walking speed, endurance, balance ability, and other abilities in children.